The tourism impact of the historical elements in the city of Jeddah - Al- Harbi, Hanadi Eid; Al- Saleh, Samirah Saad (Journal of Humanities & Social Sciences, 2021)
The main objective of this study is to try to identify the tourism components that exist in the historical area in Jeddah, and to emphasize their exploits and their usefulness, as well as the level of these elements. The study also highlighted the problems and obstacles that hinder the development of tourism in the region and the discovery of new sources of tourism. The study was conducted on tourists coming to the historic area of ​​Jeddah, Saudi Arabia, including non- Saudis during the month of the Jeddah Historical Festival (1438 H- (2017.The researcher used the questionnaire as a tool to collect her research data. The researcher has developed several questions to achieve the objectives of her research, and has used some means and statistical programs to analyze the data needed to derive the results of its study.And that the study results that resulted from this study included the disclosure of the factors and elements of tourism in the historical area in Jeddah, these factors vary in importance and the most important of these factors historical festivals.The study also showed the importance of providing tourism services and activities in sufficient and varied manner as an important tourist attraction for the historical area in Jeddah.